PELATIHAN TOEFL SEBAGAI UPAYA UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN TEST BAHASA INGGRIS BAGI MAHASISWA DI HIMPUNAN MAHASISWA HIMMAH NWDI LOMBOK TENGAH - Rosyidi, Ahmad Zuhri; Paris, Atika Salman; Hasanah, Nur Laela (LPP ARROSYIDIN, 2024)
TOEFL is an English test that is used to measure a person's English language skills. Test takers usually need the results of this test to continue their education in higher education, get job opportunities and apply for scholarships. To improve the grades and quality of their English skills, students take English courses outside of school or join special English training. Therefore, this test is considered to be very important and needs to be mastered. This test covers all the skills that must be mastered in English so it is not surprising for us to introduce this test not only for English students but for other study programs who want to learn English. The aim of this activity is to introduce types of English language tests using the TOEFL test, with the hope that this can be initial capital for students who want to continue their studies to a higher level or want to seek scholarships from the government. The outcome of this activity is that students are able to recognize and master the types of questions that will be tested in the English test so that it can help students to get maximum test results.